Genetic Defects in Children with Cardiac Anomalies/Malformations: Noonan and CFC Syndromes - Kumari, Divya; Chaudhary, Deepti; Panigrahi, Inusha; Rohit, Manoj K. (Journal of Pediatric Genetics, 2020)
Cardiac defects presenting in childhood show significant phenotypic and genetic heterogeneity. With availability of advanced genetic technologies, these can be detected early using specialized testing. Prenatal testing is currently feasible with improved ultrasonography and fetal echocardiography. Here, we report two cases of Noonan's and cardiofaciocutaneous syndromes in patients seen in the genetic unit of a tertiary care center presenting with cardiac defect with or without developmental delay, short stature, and dysmorphism. In these conditions, there is also increased risk of malignancy such as juvenile myelomonocytic leukemia. With the advent of next-generation sequencing, definitive diagnosis and counseling is possible in this group of conditions.
Keywords: dysmorphism; Noonan's syndrome; NGS; septal defect; cardiomyopathy; LZTR1